Achieving culturally competent cancer care: A qualitative study drawing on the perspectives of cancer survivors and oncology nurses - Uzar-Ozcetin, Yeter Sinem; Tee, Stephen; Kargin, Maral (Elsevier Sci Ltd, 2020)
Purpose: The aim of this study was to understand how cancer survivors and nurses define and experience cultural care and to make recommendations toward improvements in nursing practice. Methods: The study used a descriptive qualitative design. Data were collected from 29 cancer survivors and 23 oncology nurses by using in-depth semi-structured interviews. Data were transcribed and themes identified. Results: Three themes emerged from the data; 1) cross-cultural care expectations, 2) reality of cross-cultural care activities, and 3) improving culturally sensitive care. Conclusions: The data reveals that relationship between the nurse and cancer survivor is critical to an awareness of cultural needs but that nurses need help in raising their own awareness and appreciation of the benefits and impact of culturally competent care. It is only through creating self-awareness amongst nurses, in the context of each survivor and their needs and beliefs, will the standards of practice improve delivering the health outcomes that those in their care deserve.
Keywords: Cancer; Culture; Nurse; Nursing; Survivors